Respiratory presentation of diffuse idiopathic skeletal hyperostosis (DISH): Management and review of the literature. Issue 1 (2nd January 2022) - Dell'Era, Valeria; Garzaro, Massimiliano; Farri, Filippo; Gorris, Christel; Rosa, Maria Silvia; Toso, Andrea; Aluffi Valletti, Paolo
ABSTRACT: Background : Diffuse idiopathic skeletal hyperostosis (DISH) is characterized by the ossification of entheses. When localized in the cervical paravertebral region, typical signs and symptoms include stiffness, pain, loss of range of motion, and difficulty swallowing. Clinical Presentation : The authors present two less typical respiratory manifestations of DISH due to cervical osteophytes protrusion and obstruction of the upper airway. The first patient was treated conservatively (application of CPAP during nighttime), while the second required emergency intubation and a combined ENT-neurosurgical operation for the removal of osteophytes. Clinical Relevance : Even though dysphagic symptoms are more frequent, DISH may be a cause of airway obstruction and should be included in the differential diagnosis of respiratory distress and OSA.